A virtual model of the bench press exercise - Rahmani, A.; Rambaud, O.; Bourdin, M.; Mariot, J.-P. (Journal of Biomechanics, 2009)
The objective of this study was to design and validate a three degrees of freedom model in the sagittal plane for the bench press exercise. The mechanical model was based on rigid segments connected by revolute and prismatic pairs, which enabled a kinematic approach and global force estimation. The method requires only three simple measurements: (i) horizontal position of the hand (x0); (ii) vertical displacement of the barbell (Z) and (iii) elbow angle (Beta). Eight adult male throwers performed maximal concentric bench press exercises against different masses. The kinematic results showed that the vertical displacement of each segment and the global centre of mass followed the vertical displacement of the lifted mass. Consequently, the vertical velocity and acceleration of the combined centre of mass and the lifted mass were identical. Finally, for each lifted mass, there were no practical differences between forces calculated from the bench press model and those simultaneously measured with a force platform. The error was lower than 2.5%. The validity of the mechanical method was also highlighted by a standard error of the estimate (SEE) ranging from 2.0 to 6.6 N in absolute terms, a coefficient of variation (CV) 0.8%, and a correlation between the two scores 0.99 for all the lifts (p<0.001). The method described here, which is based on three simple parameters, allows accurate evaluation of the force developed by the upper limb muscles during bench press exercises in both field and laboratory conditions.